Quantum dot light-emitting device including chromium layer and method for manufacturing the same

A chromium layer between the hole transport and upper electrode in quantum dot light-emitting devices enhances stability and lifespan, addressing operational degradation issues without complex modifications, improving current density and brightness retention.

KR103042505B1Active Publication Date: 2026-11-03RES & BUSINESS FOUND SUNGKYUNKWAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020250176662
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-11-20
Publication Date
2026-11-03
Estimated Expiration
2045-11-20

AI Technical Summary

Technical Problem

Conventional quantum dot light-emitting devices face challenges in achieving long-term operational stability and lifespan due to degradation during operation, with existing solutions often requiring complex material synthesis and structural modifications that complicate manufacturing and increase costs.

Method used

Incorporating a chromium layer between the hole transport layer and the upper electrode in a quantum dot light-emitting device structure, optimizing its thickness between 2 nm to 9 nm, enhances electro-optical characteristics and driving stability without additional complexity.

Benefits of technology

The chromium layer improves current density, brightness retention, and external quantum efficiency, significantly extending the device's lifespan and maintaining excellent brightness even during prolonged operation, while simplifying the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112025130007170-PAT00001_ABST
    Figure 112025130007170-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a quantum dot light-emitting device comprising: a lower electrode disposed on a substrate; an electron transport layer disposed on the lower electrode; a quantum dot light-emitting layer disposed on the electron transport layer; a hole transport layer disposed on the quantum dot light-emitting layer; a chromium (Cr) layer disposed on the hole transport layer; and an upper electrode disposed on the chromium layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a quantum dot light-emitting device, and more specifically, to a quantum dot light-emitting device having improved driving stability and lifespan characteristics and a method for manufacturing the same. Background Technology

[0002] Quantum Dot Light Emitting Devices (QD-LEDs) have garnered attention as next-generation displays and optoelectronic devices due to their various advantages, including excellent color purity, high luminous efficiency, and the potential for large-area fabrication through solution processing. In particular, the active development of non-cadmium quantum dots, such as InP, ZnSe, and ZnTeSe, to overcome the environmental limitations of cadmium (Cd)-based quantum dots has presented the possibility of simultaneously satisfying both eco-friendliness and performance. Despite these advancements, the issue of limited device lifetimes caused by degradation during actual operation remains a significant unresolved technical challenge.

[0003] In conventional research, to address the issue of lifespan degradation, methods have been investigated such as designing novel materials capable of slowing down electrical degradation in the emissive layer (EML), hole transport layer (HTL), or electron transport layer (ETL), or using multiple charge transport layers (CTL) to prevent the accumulation and leakage of charges that cause degradation. For instance, techniques for introducing novel polymer-based HTLs, multilayer stacking structures for interface stabilization, or reducing interfacial defects through heat treatment have been reported. Furthermore, to overcome the limited thermal stability of constituent materials, alternative concepts have been proposed to improve stability, such as applying silicon substrates with excellent thermal conductivity instead of glass substrates, or minimizing power consumption for target brightness by increasing light extraction efficiency. However, most of these approaches require additional synthesis processes, the development of new materials, and complex stacking processes, which consequently have limitations in that they complicate the device fabrication process and increase manufacturing costs.

[0004] Conventional approaches proposed to date, such as replacing CTLs, introducing multilayer structures, changing substrates, and adopting top-emission structures, have all improved lifespan to a certain extent, but they have limitations in practical terms. Designing and developing new materials consumes enormous amounts of time and labor, and while efficiency and lifespan can be improved through complex device structures, design complexity can increase significantly because it entails comprehensive consideration of electrical, optical, and thermal factors. Consequently, integrating previously reported individual technologies presents a problem where the difficulty increases exponentially.

[0005] Therefore, there is a need for simple yet effective technical elements that can improve device lifespan without relying on complex material synthesis or novel structural designs. In particular, there is a demand for simple and practical device structures that can simultaneously ensure operational stability and long-term durability while maintaining electrical characteristics and external quantum efficiency.

[0006] Korean Registered Patent No. 10-0754396, which is the technology forming the background of this application, relates to a quantum dot light-emitting device and a method for manufacturing the same. The problem to be solved

[0007] The present invention aims to solve the problems of the aforementioned prior art and provides a quantum dot light-emitting device with improved driving stability and lifespan characteristics by including a chromium layer between the hole transport layer and the upper electrode.

[0008] In addition, the present invention provides a method for manufacturing a quantum dot light-emitting device that can secure enhanced electro-optical properties and long-term operating stability even with a simple process, including the step of forming a chromium layer.

[0009] In addition, the present invention provides a display device having excellent color purity and long-term reliability by including the quantum dot light-emitting element.

[0010] In addition, the present invention provides a lighting device having high luminous efficiency and long lifespan characteristics, including the above-mentioned quantum dot light-emitting element.

[0011] In addition, the present invention provides a stable and efficient optoelectronic system including the above-mentioned quantum dot light-emitting element.

[0012] However, the technical problems that the embodiments of the present invention aim to solve are not limited to the technical problems described above, and other technical problems may exist. means of solving the problem

[0013] As a technical means for achieving the above-mentioned technical problem, the first aspect of the present invention provides a quantum dot light-emitting device comprising: a lower electrode disposed on a substrate; an electron transport layer disposed on the lower electrode; a quantum dot light-emitting layer disposed on the electron transport layer; a hole transport layer disposed on the quantum dot light-emitting layer; a chromium (Cr) layer disposed on the hole transport layer; and an upper electrode disposed on the chromium layer.

[0014] According to one embodiment of the present invention, the thickness of the chromium layer may be 2 nm to 9 nm, but is not limited thereto.

[0015] According to one embodiment of the present invention, the substrate may include, but is not limited to, a glass substrate, a plastic substrate, a metal substrate, a silicon substrate, a sapphire substrate, and combinations thereof, selected from the group consisting of, but not limited to.

[0016] According to one embodiment of the present invention, the lower electrode may comprise, but is not limited to, a material selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), zinc tin oxide (ZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), and combinations thereof.

[0017] According to one embodiment of the present invention, the electron transport layer may comprise, but is not limited to, a material selected from the group consisting of ZnO, ZnMgO, TiO2, SnO2, ZrO2, and combinations thereof.

[0018] According to one embodiment of the present invention, the quantum dot light-emitting layer may comprise, but is not limited to, a material selected from the group consisting of InP, ZnSe, ZnTeSe, CdSe, CdS, PbS, PbSe, InAs, InGaP, GaP, InGaAs, InAsP, and combinations thereof.

[0019] According to one embodiment of the present invention, the hole transport layer may comprise, but is not limited to, 4,4',4''-tris(carbazole-9-yl)triphenylamine (TCTA), 4,4'-bis(N-carbazolyl)-1,1'-biphenyl (CBP), 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), N,N'-di(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine (NPB), 4,4',4''-tris[2-naphthyl(phenyl)amino]triphenylamine (2TNATA), and combinations thereof.

[0020] According to one embodiment of the present invention, the structure may further include a metal oxide-containing layer disposed between the hole transport layer and the chromium layer, but is not limited thereto.

[0021] According to one embodiment of the present invention, the metal oxide may include, but is not limited to, a material selected from the group consisting of molybdenum oxide, vanadium oxide, tungsten oxide, nickel oxide, and combinations thereof.

[0022] According to one embodiment of the present invention, the upper electrode may comprise, but is not limited to, a material selected from the group consisting of aluminum (Al), silver (Ag), gold (Au), copper (Cu), nickel (Ni), platinum (Pt), palladium (Pd), and combinations thereof.

[0023] In addition, a second aspect of the present invention provides a method for manufacturing a quantum dot light-emitting device comprising the steps of: forming an electron transport layer on a lower electrode disposed on a substrate; forming a quantum dot light-emitting layer on the electron transport layer; forming a hole transport layer on the quantum dot light-emitting layer; forming a chromium (Cr) layer on the hole transport layer; and forming an upper electrode on the chromium layer.

[0024] According to one embodiment of the present invention, the thickness of the chromium layer may be 2 nm to 9 nm, but is not limited thereto.

[0025] According to one embodiment of the present invention, the step of forming the chromium layer may be performed at a deposition rate of 0.1 Å / s to 5.0 Å / s, but is not limited thereto.

[0026] According to one embodiment of the present invention, the step of forming the chromium layer and the step of forming the upper electrode may be performed continuously without exposure to the atmosphere while maintaining a vacuum atmosphere, but are not limited thereto.

[0027] According to one embodiment of the present invention, between the step of forming the hole transport layer and the step of forming the chromium layer, the method may further include the step of forming a metal oxide-containing layer on the hole transport layer, but is not limited thereto.

[0028] In addition, the third aspect of the present invention provides a display device comprising a quantum dot light-emitting element according to the first aspect of the present invention.

[0029] In addition, the fourth aspect of the present invention provides a lighting device comprising a quantum dot light-emitting element according to the first aspect of the present invention.

[0030] In addition, the fifth aspect of the present invention provides an optoelectronic system comprising a quantum dot light-emitting element according to the first aspect of the present invention.

[0031] The means for solving the problem described above are merely exemplary and should not be interpreted as intended to limit the present invention. In addition to the exemplary embodiments described above, additional embodiments may exist in the drawings and the detailed description of the invention. Effects of the invention

[0032] The quantum dot light-emitting device according to the present invention provides excellent electro-optical characteristics and driving stability without complex material synthesis or structural modifications by introducing a chromium layer between the hole transport layer and the top electrode. Specifically, the insertion of the chromium layer significantly improves current density and brightness characteristics, and the improvement in external quantum efficiency is particularly pronounced in the high-brightness region.

[0033] Furthermore, the quantum dot light-emitting device according to the present invention exhibits a significant improvement in terms of long-term operational stability. Unlike conventional methods involving the introduction of multilayer structures or the development of new materials, the addition of a thin chromium layer significantly increases the half-life of the device, thereby greatly enhancing long-term durability. Consequently, excellent brightness retention is maintained even during prolonged operation.

[0034] Furthermore, the manufacturing method according to the present invention can be implemented by simply depositing an additional chromium layer using existing thermal vapor deposition equipment. Interfacial contamination can be prevented by continuously depositing the chromium layer and the top electrode while maintaining a vacuum atmosphere, and the manufacturing efficiency and economic feasibility are excellent in that performance improvement is possible without additional complex processes or special equipment.

[0035] The quantum dot light-emitting device according to the present invention can be applied to various fields such as displays, lighting, and optoelectronic systems, and can significantly contribute to the development of next-generation display devices that require high color purity and long lifespan. Through this, it can promote the commercialization of quantum dot light-emitting devices and contribute to the advancement of eco-friendly, high-efficiency display and lighting technologies.

[0036] However, the effects obtainable from this invention are not limited to those described above, and other effects may exist. Brief explanation of the drawing

[0037] FIG. 1 is a cross-sectional view of a quantum dot light-emitting device according to one embodiment of the present invention. FIG. 2 is a schematic diagram of a quantum dot light-emitting device according to one embodiment of the present invention. FIG. 3 is an energy level diagram of a quantum dot light-emitting device according to one embodiment of the present invention. Figure 4 is a graph showing the results of the electro-optical characteristics of a quantum dot light-emitting device (100) according to the thickness of the chromium layer. Figure 5 is a graph showing the current efficiency and luminescence efficiency of a quantum dot light-emitting device (100) according to the thickness of the chromium layer. Figure 6 is a graph showing the operating life characteristics of a quantum dot light-emitting device (100) according to the thickness of the chromium layer. Specific details for implementing the invention

[0038] Embodiments of the present invention are described below with reference to the attached drawings to enable those skilled in the art to easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein. Furthermore, in order to clearly explain the present invention in the drawings, parts unrelated to the explanation have been omitted, and similar parts throughout the specification are denoted by similar reference numerals.

[0039] Throughout this specification, when a part is described as being "connected" to another part, this includes not only cases where they are "directly connected," but also cases where they are "electrically connected" with other elements interposed between them.

[0040] Throughout the entire specification, when a component is described as being located "on," "on top," "on top," "under," "on bottom," or "on bottom" of another component, this includes not only cases where the component is in contact with the other component but also cases where another component exists between the two components.

[0041] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0042] As used herein, terms of degree such as “about,” “substantially,” etc., are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the stated meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values ​​are mentioned to aid in understanding the invention. Furthermore, throughout this specification, “a step of” or “a step of” does not mean “a step for”.

[0043] Throughout this specification, the term “combination thereof” included in the Markush-type expression means one or more mixtures or combinations selected from the group consisting of the components described in the Markush-type expression, and means including one or more selected from the group consisting of said components.

[0044] Throughout the entire specification, the description "A and / or B" means "A, B, or A and B".

[0045] Hereinafter, the quantum dot light-emitting device of the present invention and the method for manufacturing the same will be described in detail with reference to the embodiments, examples, and drawings. However, the present invention is not limited to these embodiments, examples, and drawings.

[0047] FIG. 1 is a cross-sectional view of a quantum dot light-emitting device (100) according to one embodiment of the present invention.

[0048] As a technical means for achieving the above-mentioned technical problem, the first aspect of the present invention provides a quantum dot light-emitting device (100) comprising: a lower electrode (20) disposed on a substrate (10); an electron transport layer (30) disposed on the lower electrode (20); a quantum dot light-emitting layer (40) disposed on the electron transport layer (30); a hole transport layer (50) disposed on the quantum dot light-emitting layer (40); a chromium (Cr) layer (60) disposed on the hole transport layer (50); and an upper electrode (70) disposed on the chromium layer (60).

[0049] The quantum dot light-emitting device (100) according to the present invention has a structure in which the substrate (10) is sequentially stacked to the upper electrode (70), and is characterized in that a chromium layer (60) is disposed between the hole transport layer (50) and the upper electrode (70). The chromium layer (60) plays a role in improving the electro-optical characteristics and driving stability of the device by improving electrical and chemical stability at the interface between the hole transport layer (50) and the upper electrode (70). Specifically, the introduction of the chromium layer (60) improves current density and brightness characteristics and prevents a decrease in external quantum efficiency even in high brightness regions. In addition, it provides the effect of significantly extending the lifespan of the device by improving the brightness retention rate during long-term operation.

[0050] According to one embodiment of the present invention, the thickness of the chromium layer (60) may be 2 nm to 9 nm, but is not limited thereto.

[0051] The thickness of the chromium layer (60) is a factor that significantly affects the performance of the quantum dot light-emitting device (100). If the thickness of the chromium layer (60) is excessively thin, less than 2 nm, the interface stabilization effect between the hole transport layer (50) and the upper electrode (70) is insufficient, so the effect of improving driving stability is not clearly observed. On the other hand, if the thickness of the chromium layer (60) is excessively thick, exceeding 9 nm, charge injection is inhibited, causing the onset voltage to rise, the external quantum efficiency to drop sharply, and the driving stability to show a tendency to decrease. Therefore, it is preferable that the thickness of the chromium layer (60) be formed in the range of 2 nm to 9 nm.

[0052] More preferably, the thickness of the chromium layer (60) may be 4 nm to 6 nm, and most preferably about 5 nm. In this optimal thickness range, the balance of charge injection characteristics, external quantum efficiency, and operating life is optimized so that the overall performance of the quantum dot light-emitting device (100) can be maximized.

[0053] According to one embodiment of the present invention, the substrate (10) may include, but is not limited to, a glass substrate, a plastic substrate, a metal substrate, a silicon substrate, a sapphire substrate, and combinations thereof.

[0054] The glass substrate used as the substrate (10) provides excellent optical transparency and surface flatness, making it suitable for general display applications, while the plastic substrate can be applied to flexible displays requiring flexibility and lightness. The silicon substrate has high thermal conductivity, allowing it to effectively dissipate heat generated during operation, and the sapphire substrate provides excellent mechanical strength and chemical stability. The metal substrate has excellent electrical and thermal conductivity and can be used for specific applications. The selection of the substrate (10) can be determined by considering the end use of the quantum dot light-emitting device (100), the required physical properties, and the compatibility of the manufacturing process.

[0055] According to one embodiment of the present invention, the lower electrode (20) may comprise, but is not limited to, a material selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), zinc tin oxide (ZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), and combinations thereof.

[0056] The lower electrode (20) above serves as an electrode that supplies power to the quantum dot light-emitting device (100) and functions to inject electrons into the electron transport layer (30). The lower electrode (20) must possess excellent electrical conductivity and light transmittance simultaneously, and the energy level alignment with the electron transport layer (30) must be appropriate so that efficient electron injection is possible. The transparent conductive oxides above are suitable as materials for the lower electrode (20) because they exhibit high transmittance in the visible light region while having low electrical resistance. In particular, ITO is the most widely used material for the lower electrode (20) because it has high transparency, excellent electrical conductivity, and chemical stability.

[0057] According to one embodiment of the present invention, the electron transport layer (30) may comprise, but is not limited to, a material selected from the group consisting of ZnO, ZnMgO, TiO2, SnO2, ZrO2, and combinations thereof.

[0058] The electron transport layer (30) serves to efficiently transfer electrons injected from the lower electrode (20) to the quantum dot light-emitting layer (40). The electron transport layer (30) has high electron mobility and hole blocking characteristics, thereby improving the recombination efficiency of electrons and holes within the quantum dot light-emitting layer (40). The metal oxide materials have appropriate electron affinity, which lowers the electron injection barrier from the lower electrode (20), and are chemically stable, thereby improving the durability of the device. In particular, ZnMgO can control energy levels by adjusting the Mg content, allowing for the optimization of interface characteristics with the quantum dot light-emitting layer (40). The electron transport layer (30) can be formed by a solution process or a vacuum deposition method, and the formation of a uniform thin film has an important impact on device performance.

[0059] According to one embodiment of the present invention, the quantum dot light-emitting layer (40) may comprise, but is not limited to, a material selected from the group consisting of InP, ZnSe, ZnTeSe, CdSe, CdS, PbS, PbSe, InAs, InGaP, GaP, InGaAs, InAsP, and combinations thereof.

[0060] The above quantum dot light-emitting layer (40) is a core component of the quantum dot light-emitting device (100) and is a layer in which electrons injected from the electron transport layer (30) and holes injected from the hole transport layer (50) recombine to emit light. Quantum dots are nanometer-sized semiconductor particles, and precise control of the emission wavelength is possible through size adjustment via the quantum confinement effect. This enables the realization of high color purity and a wide color reproduction rate. In particular, non-cadmium quantum dots such as InP, ZnSe, and ZnTeSe exhibit excellent light-emitting characteristics while complying with environmental regulations. The thickness of the quantum dot light-emitting layer (40) can be optimized for efficient charge recombination and high light-emitting efficiency.

[0061] According to one embodiment of the present invention, the hole transport layer (50) may comprise, but is not limited to, 4,4',4''-tris(carbazole-9-yl)triphenylamine (TCTA), 4,4'-bis(N-carbazolyl)-1,1'-biphenyl (CBP), 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), N,N'-di(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine (NPB), 4,4',4''-tris[2-naphthyl(phenyl)amino]triphenylamine (2TNATA), and combinations thereof.

[0062] The hole transport layer (50) serves to efficiently transport holes injected from the upper electrode (70) to the quantum dot light-emitting layer (40). The hole transport layer (50) has high hole mobility and exhibits electron blocking characteristics, thereby inducing balanced recombination of electrons and holes within the quantum dot light-emitting layer (40). The hole transport materials have appropriate HOMO (Highest Occupied Molecular Orbital) energy levels, which lower the barrier to hole injection from the upper electrode (70) and facilitate the transport of holes to the quantum dot light-emitting layer (40). TCTA has excellent hole transport characteristics and thermal stability, so it is widely used in quantum dot light-emitting devices (100) formed by vacuum deposition. Since the thickness and characteristics of the hole transport layer (50) have a significant impact on the electro-optical performance of the device, they must be optimized by considering the balance with the quantum dot light-emitting layer (40) and the electron transport layer (30).

[0063] According to one embodiment of the present invention, the structure may further include a metal oxide-containing layer disposed between the hole transport layer (50) and the chromium layer (60), but is not limited thereto.

[0064] The metal oxide-containing layer can be selectively placed between the hole transport layer (50) and the chromium layer (60) and serves to further improve hole injection efficiency. The metal oxide-containing layer increases the electrical conductivity of the hole transport layer (50) and reduces the hole injection barrier from the upper electrode (70), thereby lowering the driving voltage of the device and improving current efficiency. Additionally, the metal oxide-containing layer improves the interface characteristics between the hole transport layer (50) and the chromium layer (60), thereby improving the uniformity of charge transfer.

[0065] The metal oxide-containing layer can be formed by depositing the metal oxide alone or by a co-evaporation method in which the hole transport material and the metal oxide are deposited simultaneously. In the case of a metal oxide-only layer, it can be formed by sequentially depositing the metal oxide in a vacuum atmosphere after forming the hole transport layer (50). Meanwhile, the co-evaporation structure has a form in which the metal oxide is dispersed within the matrix of the hole transport material, and efficient hole injection and transport are possible by combining the high work function of the metal oxide and the excellent hole mobility of the hole transport material. As the hole transport material, a material identical or similar to the material used in the hole transport layer (50) may be used, and preferably, TCTA may be used. By independently controlling the deposition rate of each material during co-evaporation, the concentration of the metal oxide within the metal oxide-containing layer can be controlled, thereby optimizing the electrical characteristics of the metal oxide-containing layer.

[0066] According to one embodiment of the present invention, the metal oxide may include, but is not limited to, a material selected from the group consisting of molybdenum oxide, vanadium oxide, tungsten oxide, nickel oxide, and combinations thereof.

[0067] The above metal oxides have a high work function and play a role in improving hole injection characteristics. In particular, molybdenum oxide (MoOx) has a high work function of about 6.7 eV, which can significantly lower the hole injection barrier from the top electrode (70) and can be formed stably in a vacuum deposition process. Vanadium oxide (V2O5) and tungsten oxide (WO3) also exhibit similar hole injection characteristics. These metal oxides can be formed as a single layer or co-deposited with a hole transport material to provide a p-doping effect, improve the electrical conductivity of the hole transport layer (50) or the metal oxide-containing layer, and contribute to lowering the driving voltage of the device and increasing current efficiency.

[0068] According to one embodiment of the present invention, the upper electrode (70) may comprise, but is not limited to, a material selected from the group consisting of aluminum (Al), silver (Ag), gold (Au), copper (Cu), nickel (Ni), platinum (Pt), palladium (Pd), and combinations thereof.

[0069] The upper electrode (70) above serves as an electrode that supplies power to the quantum dot light-emitting device (100) and functions to inject holes into the hole transport layer (50) through the chromium layer (60). The upper electrode (70) must have low electrical resistance and high reflectivity, and must exhibit good contact characteristics with the chromium layer (60). Aluminum (Al) is the most widely used material for the upper electrode (70) because it has a low work function, excellent electrical conductivity, high reflectivity, and cost-effectiveness. In particular, the combination of the chromium layer (60) and the aluminum upper electrode (70) in the present invention has excellent interfacial stability, which greatly improves long-term operating stability. Silver (Ag) has the highest electrical conductivity and light reflectivity, but its chemical stability may be relatively low. Gold (Au) and platinum (Pt) have excellent chemical stability and are suitable for applications requiring a long lifespan. The thickness of the upper electrode (70) is determined by considering electrical resistance and optical properties, and is generally formed in the range of tens to hundreds of nanometers.

[0070] Additionally, a second aspect of the present invention provides a method for manufacturing a quantum dot light-emitting device (100), comprising the steps of: forming an electron transport layer (30) on a lower electrode (20) disposed on a substrate (10); forming a quantum dot light-emitting layer (40) on the electron transport layer (30); forming a hole transport layer (50) on the quantum dot light-emitting layer (40); forming a chromium (Cr) layer (60) on the hole transport layer (50); and forming an upper electrode (70) on the chromium layer (60).

[0071] Regarding the manufacturing method according to the second aspect of the present invention, detailed descriptions of parts that overlap with the first aspect of the present invention have been omitted, but even if such descriptions are omitted, the contents described in the first aspect of the present invention can be applied equally to the second aspect of the present invention.

[0072] A method for manufacturing a quantum dot light-emitting device (100) according to the present invention comprises steps for sequentially forming each functional layer, and is characterized in that it includes a step for forming a chromium layer (60). The manufacturing process may be performed by a combination of a solution process and a vacuum deposition process, and the conditions for forming each layer are controlled to optimize the performance of the device. The electron transport layer (30) and the quantum dot light-emitting layer (40) may be formed by a solution process, and the hole transport layer (50), the metal oxide-containing layer, the chromium layer (60), and the top electrode (70) may be formed by a vacuum thermal evaporation method. After the formation of each layer, an appropriate heat treatment or drying process may be performed, and the finally completed device may be encapsulated to protect it from oxygen and moisture.

[0073] According to one embodiment of the present invention, the thickness of the chromium layer may be 2 nm to 9 nm, but is not limited thereto.

[0074] According to one embodiment of the present invention, the step of forming the chromium layer may be performed at a deposition rate of 0.1 Å / s to 5.0 Å / s, but is not limited thereto.

[0075] In the step of forming the chromium layer (60), the deposition rate is an important process variable that affects the film quality and interface characteristics of the chromium layer (60). If the deposition rate is excessively slow, such as less than 0.1 Å / s, the process time becomes excessively long, which reduces productivity and increases the possibility of contamination by residual impurities in the vacuum chamber. On the other hand, if the deposition rate is excessively fast, such as exceeding 5.0 Å / s, the uniformity of the chromium layer (60) decreases and the density of the film quality decreases, which may reduce the electrical characteristics and stability of the device. Therefore, it is preferable that the deposition of the chromium layer (60) be performed at a rate of 0.1 Å / s to 5.0 Å / s, and more preferably at a rate of 0.5 Å / s to 1.0 Å / s. Within this appropriate deposition rate range, a uniform and dense chromium layer (60) is formed, thereby optimizing the interface stability between the hole transport layer (50) and the upper electrode (70).

[0076] According to one embodiment of the present invention, the step of forming the chromium layer (60) and the step of forming the upper electrode (70) may be performed continuously without exposure to the atmosphere while maintaining a vacuum atmosphere, but are not limited thereto. .

[0077] Continuously depositing the chromium layer (60) and the upper electrode (70) in a vacuum atmosphere is intended to prevent the surface of the chromium layer (60) from being exposed to oxygen or moisture in the atmosphere and oxidizing. If the surface of the chromium layer (60) oxidizes, the interfacial resistance between the chromium layer (60) and the upper electrode (70) increases, hole injection characteristics deteriorate, and interfacial deterioration may be accelerated during long-term operation. Therefore, a clean interface can be secured by continuously depositing the upper electrode (70) within the same vacuum chamber or in another chamber connected while maintaining a vacuum, without destroying the vacuum immediately after the chromium layer (60) is formed. This continuous deposition process improves the electrical contact characteristics between the chromium layer (60) and the upper electrode (70) and provides the effect of significantly improving the operating stability and lifespan of the device.

[0078] According to one embodiment of the present invention, between the step of forming the hole transport layer (50) and the step of forming the chromium layer (60), the method may further include the step of forming a metal oxide-containing layer on the hole transport layer (50), but is not limited thereto.

[0079] The step of forming the metal oxide-containing layer can be performed by depositing the metal oxide alone or by co-depositing the hole transport material and the metal oxide. In the case of depositing the metal oxide alone, the metal oxide layer can be formed by depositing the metal oxide while maintaining a vacuum atmosphere after forming the hole transport layer (50). Meanwhile, the co-depositing process is performed by simultaneously depositing the hole transport material and the metal oxide using two independent evaporation sources. By independently controlling the temperature of each evaporation source, the deposition rate of each material can be controlled, thereby allowing for precise control of the metal oxide doping concentration within the metal oxide-containing layer. For example, when TCTA is used as the hole transport material and MoOx is used as the metal oxide, the target doping concentration can be achieved by adjusting the deposition rate of TCTA and the deposition rate of MoOx in an appropriate ratio. The thickness of the metal oxide-containing layer is determined by considering the hole injection characteristics and the overall device structure, and can generally be formed in the range of several nanometers to tens of nanometers. The co-deposition process can be easily implemented in vacuum thermal evaporation equipment and is suitable for mass production due to its excellent reproducibility.

[0080] In addition, the third aspect of the present invention provides a display device comprising a quantum dot light-emitting element (100) according to the first aspect of the present invention.

[0081] Regarding the display device according to the third aspect of the present invention, detailed descriptions of parts that overlap with the first aspect of the present invention have been omitted, but even if such descriptions are omitted, the contents described in the first aspect of the present invention may be applied equally to the third aspect of the present invention.

[0082] The above display device may be configured using a quantum dot light-emitting element (100) according to the present invention as a pixel. The excellent color purity and high luminous efficiency of the quantum dot light-emitting element (100), and the improved driving stability resulting from the introduction of the chrome layer (60) of the present invention, enable the realization of a high-definition display. The display device may be configured as an active matrix or a passive matrix, and a full-color display can be realized by arranging quantum dot light-emitting elements (100) that emit red, green, and blue light. Due to the long lifespan characteristics of the quantum dot light-emitting element (100) according to the present invention, the lifespan of the display is extended, and stable image quality can be maintained even during long-term use. Such a display device can be applied to various electronic products such as televisions, monitors, smartphones, tablets, and wearable devices.

[0083] Additionally, the fourth aspect of the present invention provides a lighting device comprising a quantum dot light-emitting element (100) according to the first aspect of the present invention.

[0084] Regarding the lighting device according to the fourth aspect of the present invention, detailed descriptions of parts that overlap with the first aspect of the present invention have been omitted, but even if such descriptions are omitted, the contents described in the first aspect of the present invention may be applied equally to the fourth aspect of the present invention.

[0085] The above lighting device may be configured using a quantum dot light-emitting element (100) according to the present invention as a light source. The quantum dot light-emitting element (100) can provide high luminous efficiency and excellent color rendering to realize high-quality lighting. In particular, for white light emission, red, green, and blue quantum dot light-emitting elements (100) may be combined, or a blue quantum dot light-emitting element (100) may be combined with a color-changing quantum dot. The improved driving stability and long lifespan characteristics resulting from the introduction of the chromium layer (60) of the present invention extend the maintenance cycle of the lighting device and improve reliability. Such a lighting device can be applied to various fields such as general lighting, industrial lighting, automotive lighting, and medical lighting, and can be utilized as an eco-friendly lighting solution due to its high energy efficiency.

[0086] Additionally, the fifth aspect of the present invention provides an optoelectronic system comprising a quantum dot light-emitting element (100) according to the first aspect of the present invention.

[0087] Regarding the optoelectronic system according to the fifth aspect of the present invention, detailed descriptions of parts that overlap with the first aspect of the present invention have been omitted, but even if such descriptions are omitted, the contents described in the first aspect of the present invention may be applied equally to the fifth aspect of the present invention.

[0088] The above optoelectronic system refers to an integrated optical and electronic system comprising a quantum dot light-emitting element (100) according to the present invention as a core component. The optoelectronic system may include an optical communication system, an optical sensor, a biosensor, an optical signal processing device, etc. The narrow emission spectrum and high color purity of the quantum dot light-emitting element (100) are advantageous for the generation and processing of precise optical signals, and the enhanced driving stability ensures reliability in systems requiring continuous operation for a long time. In addition, the fast response speed of the quantum dot light-emitting element (100) is suitable for applications requiring high-speed optical communication or high-frequency modulation. An optoelectronic system including the quantum dot light-emitting element (100) according to the present invention can be utilized in various advanced technology fields such as medical diagnosis, environmental monitoring, security systems, and data communication.

[0089] The present invention is to be explained in more detail through the following examples, but the following examples are for illustrative purposes only and are not intended to limit the scope of the present invention.

[0091] [Example 1] Preparation of a quantum dot light-emitting device including a chromium layer

[0092] In this embodiment, a quantum dot light-emitting device including a chromium layer between the hole transport layer and the upper electrode was manufactured as follows.

[0093] First, a substrate with a pre-patterned ITO (Indium Tin Oxide) was prepared and ultrasonically cleaned with acetone and isopropyl alcohol (IPA), respectively. The cleaned substrate was dried in a 60°C oven.

[0094] An electron transport layer precursor solution was spin-coated onto a cleaned ITO substrate at 4,000 rpm for 30 seconds to form a thin film approximately 30 nm thick. The deposited thin film was heat-treated by baking at 180 ℃ for 30 minutes, and then cooled to room temperature.

[0095] A quantum dot solution was spin-coated on the above ITO / ETL substrate at 4,000 rpm for 30 seconds to form quantum dots having an InP / ZnSe / ZnS structure of approximately 1.5 monolayers. The formed QD thin film was dried at 90 ℃ for 30 minutes.

[0096] The substrate with the formed ITO / ETL / QD structure was transferred to a vacuum thermal evaporator. 1×10 -6 TCTA 55 nm was deposited under pressure conditions below Torr, with the deposition rate controlled to 0.6 Å / s. Subsequently, MoO x A metal oxide-containing layer (total 15 nm) was formed by simultaneously depositing TCTA, and the deposition rate was MoO x The deposition rate was controlled at 0.4 Å / s and TCTA at 0.2 Å / s. Cr was deposited at 5 nm on top, with the deposition rate controlled at 0.5–1.0 Å / s. Finally, an Al electrode was deposited at 100 nm, with the deposition rate controlled at 1.0 Å / s.

[0097] To prevent degradation caused by oxygen and moisture in the air, the finished components were encapsulated inside a glove box. The encapsulated components were stored in an inert atmosphere.

[0098] Quantum dot light-emitting devices were fabricated by varying the thickness of the chromium layer to 0 nm, 1 nm, 5 nm, and 10 nm using the above method.

[0099] As shown in Fig. 2, the actual fabricated quantum dot light-emitting device comprises an ITO bottom electrode, an electron transport layer composed of ZnMgO nanoparticles, a quantum dot light-emitting layer, a hole transport layer composed of TCTA, and TCTA:MoO x It can be confirmed that it was fabricated with a structure comprising a metal oxide-containing layer composed of, a chromium layer composed of Cr, and an upper electrode composed of Al.

[0101] [Experimental Example 1] Energy Level Analysis of Quantum Dot Light Emitting Devices

[0102] Figure 3 is an energy level diagram of a quantum dot light-emitting device fabricated by introducing Cr.

[0103] Referring to FIG. 3, this diagram is an energy level structure diagram illustrating the energy barriers and charge transport paths encountered when charges (electrons and holes) are injected into the emissive layer. Electrons are injected from the left electrode, ITO, pass through the ZnMgO electron transport layer (ETL), and then move to the emissive layer. On the other hand, holes are injected from the right electrode, Al, and then sequentially pass through the Cr layer, the TCTA:MoOx layer, and the TCTA hole transport layer to be transferred to the emissive layer. As charges are injected into the emissive layer by passing through each layer in this manner, electrons and holes recombine in the emissive layer to emit light. The arrows indicated in the diagram represent the direction of injection and the transport path of these charges.

[0104] [Experimental Example 2] Analysis of Electro-optical Properties According to Chromium Layer Thickness

[0105] Electro-optical properties were measured for quantum dot light-emitting devices with different thicknesses of the chromium layer fabricated in the above example.

[0106] Figure 4 shows the results of the electro-optical characteristics of the quantum dot light-emitting device according to the thickness of Cr.

[0107] Referring to Figure 4, the current density-voltage characteristics, luminance-voltage characteristics, and external quantum efficiency (EQE)-current density characteristics are plotted to evaluate the electrical and optical characteristics that appear when voltage is applied to the device. Through this, it is possible to quantitatively determine how much current flows within the device when voltage is applied, at what level of luminescence occurs, and how efficiently the generated light is emitted.

[0108] As a result of measurements taken for chromium layer thicknesses of 0 nm, 1 nm, 5 nm, and 10 nm, the current density and luminance characteristics were noticeably improved with the introduction of the chromium layer, and the best characteristics were exhibited in devices containing a 5 nm thick chromium layer. On the other hand, devices containing a 10 nm thick chromium layer showed a tendency for current density and luminance to decrease significantly. In particular, by comparing the changes in electrical and optical performance according to the change in the thickness of the Cr layer, it was possible to evaluate the influence of the Cr layer on the charge injection and luminous efficiency characteristics of the device.

[0109] Table 1 below summarizes the maximum current and maximum brightness of quantum dot light-emitting devices according to Cr thickness.

[0110] Cr 두께 (nm) 0 1 5 10 Maximum current (mA / cm²) 2 ) 2799.495 3342.526 3580.434 587.1531 Maximum luminance (cd / m²) 2 ) 9491.087 15848.39 34251.09 5263.622

[0111] As shown in Table 1, the maximum current flow and maximum brightness levels within the device were quantitatively determined according to the Cr layer thickness (0, 1, 5, 10 nm). When the chromium layer thickness was 5 nm, the maximum current density was 3580.434 mA / cm² and the maximum brightness was 34251.09 cd / m², showing the highest values. Compared to the control group without a chromium layer (0 nm), the maximum brightness of the device containing the 5 nm chromium layer increased by approximately 3.6 times. On the other hand, the maximum current and maximum brightness of the device containing the 10 nm thick chromium layer decreased significantly due to inhibited charge injection.

[0112] [Experimental Example 3] Analysis of Current Efficiency and Luminous Efficiency According to Chromium Layer Thickness

[0113] Current efficiency and luminescence efficiency were measured for quantum dot light-emitting devices with different thicknesses of the chromium layer fabricated in the above example.

[0114] Figure 5 shows the measurement results of current efficiency and luminous efficiency according to the thickness of Cr.

[0115] Referring to Figure 5, in order to evaluate the luminescence performance of the device from various angles, the changes in current efficiency and luminous efficiency according to current density were respectively plotted.

[0116] Current efficiency is an indicator representing the amount of light generated relative to the injected current, while luminous efficiency is an indicator that evaluates luminescent performance relative to power consumption, allowing for an intuitive assessment of the device's energy conversion efficiency. Measurements taken for chromium layer thicknesses of 0 nm, 1 nm, 5 nm, and 10 nm showed a tendency for current efficiency and luminous efficiency to improve with the introduction of the chromium layer. In particular, devices containing a 5 nm thick chromium layer maintained excellent current and luminous efficiencies even in high current density regions. Conversely, devices containing a 10 nm thick chromium layer showed a tendency for current and luminous efficiencies to drop sharply. These results clearly demonstrate the impact of changes in Cr layer thickness on the device's luminescent characteristics and power efficiency.

[0117] [Experimental Example 4] Analysis of Device Lifetime Characteristics According to Chromium Layer Thickness

[0118] For quantum dot light-emitting devices with different thicknesses of the chrome layer fabricated in the above example, the operating life was measured under an initial brightness of 800 nit.

[0119] Figure 6 shows the measurement results of the device lifetime (initial brightness 800 nit) of a quantum dot light-emitting device according to the thickness of Cr.

[0120] Referring to Fig. 6, the changes in relative luminance and normalized relative luminance over time were shown when the device was driven under initial luminance conditions (800 nit). By comparing how the device's luminance retention characteristics varied according to Cr layer thicknesses (0, 1, 5, 10 nm), the device's stability and degradation rate could be evaluated based on the degree of luminance reduction over driving time. The measurement results showed that the device's lifespan was significantly improved with the introduction of a chromium layer, and the device containing a 5 nm thick chromium layer exhibited the best lifespan characteristics. In other words, this graph clearly demonstrates the effect of changes in Cr thickness on the device's luminance stability during long-term operation under the same conditions.

[0121] Table 2 summarizes the changes in device lifespan characteristics according to Cr thickness.

[0122] Cr 두께 (nm) 0 1 5 10 LT 80 (hours) 0.015 0.24 0.525 0.015 LT 70 (hours) 0.03 0.48 1.23 0.03 LT 60 (hours) 0.06 1.005 3.24 0.06 LT 50 (hours) 0.13 2.16 14.1 0.12

[0123] Referring to Table 2, to compare the lifetime characteristics of the device according to the Cr layer thickness (0, 1, 5, 10 nm), the operating time until reaching a specific brightness decrease point (LT 80, LT 70, LT 60, LT 50) was quantitatively expressed. The half-life (LT50) of the control group (0 nm) without a chromium layer was 0.13 hours, but the half-life of the device containing a 5 nm thick chromium layer increased to 14.1 hours, which is about 108 times. The device containing a 1 nm thick chromium layer also showed an improved half-life of 2.16 hours, but exhibited a lower lifetime than the device with a 5 nm thickness. On the other hand, the device containing a 10 nm thick chromium layer showed a half-life of 0.12 hours, which is similar to the control group, confirming that an excessively thick chromium layer actually has a negative effect on the device lifetime.

[0124] These results indicate that the introduction of a chromium layer improves the interface characteristics between the hole transport layer and the top electrode, thereby significantly improving the brightness retention rate during long-term operation, and particularly that the balance of current density, brightness, external quantum efficiency, and lifetime is optimized in an optimal thickness range of 2 nm to 9 nm, more preferably 4 nm to 6 nm, and most preferably about 5 nm.

[0126] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical concept or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form.

[0127] The scope of the present invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning and scope of the claims and the concept of equivalents thereof should be interpreted as being included within the scope of the present invention. Explanation of the symbols

[0128] 10: Substrate 20: Lower electrode 30: Electron transport layer 40: Quantum dot emissive layer 50: Precision Transport Layer 60: Chromium layer 70: Upper electrode 100: Quantum dot light-emitting device

Claims

Claim 1 A quantum dot light-emitting device comprising: a lower electrode disposed on a substrate; an electron transport layer disposed on the lower electrode; a quantum dot light-emitting layer disposed on the electron transport layer; a hole transport layer disposed on the quantum dot light-emitting layer; a chromium (Cr) layer disposed on the hole transport layer; and an upper electrode disposed on the chromium layer; and further comprising a metal oxide-containing layer disposed between the hole transport layer and the chromium layer. Claim 2 A quantum dot light-emitting device according to claim 1, characterized in that the thickness of the chromium layer is 2 nm to 9 nm. Claim 3 A quantum dot light-emitting device according to claim 1, wherein the substrate comprises a glass substrate, a plastic substrate, a metal substrate, a silicon substrate, a sapphire substrate, and combinations thereof. Claim 4 A quantum dot light-emitting device according to claim 1, wherein the lower electrode comprises a material selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), zinc tin oxide (ZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), and combinations thereof. Claim 5 A quantum dot light-emitting device according to claim 1, wherein the electron transport layer comprises a material selected from the group consisting of ZnO, ZnMgO, TiO2, SnO2, ZrO2, and combinations thereof. Claim 6 A quantum dot light-emitting device according to claim 1, wherein the quantum dot light-emitting layer comprises a material selected from the group consisting of InP, ZnSe, ZnTeSe, CdSe, CdS, PbS, PbSe, InAs, InGaP, GaP, InGaAs, InAsP, and combinations thereof. Claim 7 A quantum dot light-emitting device according to claim 1, wherein the hole transport layer comprises a material selected from the group consisting of 4,4',4''-tris(carbazole-9-yl)triphenylamine (TCTA), 4,4'-bis(N-carbazolyl)-1,1'-biphenyl (CBP), 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), N,N'-di(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine (NPB), 4,4',4''-tris[2-naphthyl(phenyl)amino]triphenylamine (2TNATA), and combinations thereof. Claim 8 delete Claim 9 A quantum dot light-emitting device according to claim 1, wherein the metal oxide comprises a material selected from the group consisting of molybdenum oxide, vanadium oxide, tungsten oxide, nickel oxide, and combinations thereof. Claim 10 A quantum dot light-emitting device according to claim 1, wherein the upper electrode comprises a material selected from the group consisting of aluminum (Al), silver (Ag), gold (Au), copper (Cu), nickel (Ni), platinum (Pt), palladium (Pd), and combinations thereof. Claim 11 A method for manufacturing a quantum dot light-emitting device comprising: a step of forming an electron transport layer on a lower electrode disposed on a substrate; a step of forming a quantum dot light-emitting layer on the electron transport layer; a step of forming a hole transport layer on the quantum dot light-emitting layer; a step of forming a chromium (Cr) layer on the hole transport layer; and a step of forming an upper electrode on the chromium layer; wherein, between the step of forming the hole transport layer and the step of forming the chromium layer, the method further comprises a step of forming a metal oxide-containing layer on the hole transport layer. Claim 12 A method for manufacturing a quantum dot light-emitting device according to claim 11, characterized in that the thickness of the chromium layer is 2 nm to 9 nm. Claim 13 A method for manufacturing a quantum dot light-emitting device according to claim 11, characterized in that the step of forming the chromium layer is performed at a deposition rate of 0.1 Å / s to 5.0 Å / s. Claim 14 A method for manufacturing a quantum dot light-emitting device according to claim 11, wherein the step of forming the chromium layer and the step of forming the upper electrode are performed continuously without exposure to the atmosphere while maintaining a vacuum atmosphere. Claim 15 delete Claim 16 A display device comprising a quantum dot light-emitting element according to claim 1. Claim 17 A lighting device comprising a quantum dot light-emitting element according to claim 1. Claim 18 An optoelectronic system comprising a quantum dot light-emitting element according to claim 1.

Citation Information

Patent Citations

  • Self-luminous element, manufacturing method of the same, self-luminous display device, and electronic device

    JP2020155766A

  • Light emitting diode and light emitting device including the same

    KR1020210028410A

  • Substrate optimization system for flexible quantum dot light-emitting diodes

    KR1020250107746A